Integrated Reporting as a Tool for Communicating with Stakeholders – Advantages and Disadvantages - Matuszyk Iwona; Rymkiewicz Bartosz (E3S Web of Conferences, 2018)
Financial and non-financial reporting from the beginning of its existence is the primary source of communication between the company and a wide range of stakeholders. Over the decades it has adapted to the needs of rapidly changing business and social environment. Currently, the final link in the evolution of organizational reporting, such as integrated reporting, assumes integration and mutual connectivity to both financial and non-financial data. The main interest in the concept of integrated reporting comes from the value it contributes to the organization. Undoubtedly, the concept of integrated reporting is a milestone in the evolution of organizational reporting. It is however important to consider whether it adequately addresses the information needs of a wide range of stakeholders, and whether it is a universal tool for communication between the company and its stakeholders. The aim of the paper is to discuss the advantages and disadvantages of the concept of integrated reporting as a tool for communication with stakeholders and to further directions of its development. The article uses the research methods such as literature analysis, the content analysis of the corporate publications and comparative analysis.